Study on the Development of Passive MR Damper with Displacement-Dependent Damping Characteristics - Takahiro MURAKAMI; Michiya SAKAI; Masami NAKANO (Journal of Fluid Science and Technology, 2010)
In this paper, we propose a new concept of a magneto-rheological (MR) fluid damper, which is a passive MR fluid damper. The passive MR damper has no electrical devices, such as a sensor, power supply and controller, and hence, it has an advantage in reliability and cost compared with semi-active MR dampers. Moreover, the proposed MR damper can be designed to have a variable damping force in response to its displacement. In this paper, the dynamic performance of the passive MR damper is experimentally demonstrated. The prototype of the proposed damper has been manufactured in order to verify the dynamic performance. The displacement excitation test result of the damper demonstrates that the damping characteristics depend on its displacement amplitude, that is, the damper behaves as a linear viscous damper under small vibrations and develops much higher damping performance under large vibrations.